HUBUNGAN POLA ASUH ORANG TUA DENGAN AKTUALISASI DIRI PADA REMAJA DI SMP MUHAMMADIYAH 3 YOGYAKARTA - Hanne Komalaningrum (FKU 15 UMY 616, 2015)
Adolescence is atransition phase from childhood to adulthood. Understanding of self-actualization less is very harmful for adolescent. One important factor that correlate with self-actualization is parenting pattern.Proper parental care pattern will give a huge impact for adolescent. It was the adolescent ‘s ability to express herself without feeling depressed and afraid to be wrong in making any decision. The purpose of this research was to find the correlations parenting pattern with self-actualization of adolescent at SMP Muhammadiyah 3 Yogyakarta. Methods : The research was cross sectional descriptive analytic approach. The sampling technique used was random sampling with 161 respondents. Result : Results showed that most parents in upbringing of democratic categories 85,1%, and most self-actualization of adolescent in moderate category it was 84,5%. The results of Spearman’s rho correlation test showed r values 0,179 with p value of 0,023. Conclusion : Based on these results, there were significant correlations between parenting pattern with self-actualization of adolescent at SMP Muhammadiyah 3 Yogyakarta. Keywords :Adolescent, parenting pattern, self-actualization.